Effect of molecular structure on pyrolysis coking performances of hydrocarbons at different temperatures. (15th October 2022) - Li, Haowen; Wu, Yong; Yang, Zixin; Song, Qianshi; Zhang, Jie; Wang, Xiaohan
Highlights: Compared with nC7, MCH has lower heat sink at low temperature and higher coking rate at high temperature. The unique unimolecular demethylation and intramolecular stepwise dehydrogenation reactions of MCH caused its coking rate to be higher than that of nC7. An experimental parameter for evaluating coking active site density for irregular coke morphology was proposed. Some five-membered ring hydrocarbons such as cyclopentenes and PAHs such as A3-A5 components were considered as possible additional coking precursors. The wall coking can be divided into several steps, in which the filamentous coke produced by catalytic coking provides the initial coking sites. Abstract: Methylcyclohexane (MCH) and n -heptane (nC7) were used to perform experimental studies in high-temperature oxidation pretreated STS304 reactor (ϕ2 × 0.5 × 1000 mm) at 873–1073 K, 1.0 MPa, and 1.0 mL/min feed rate. The heat sinks of the two fuels were calculated based on the conversion and product distribution. MCH was found to have difficulty in achieving high heat sink at low and high temperatures. The formation pathways of ethylene and benzene were then compared. Results showed their main precursors were similar, but the contribution proportion of each path was different affected by initial cracking reactions of MCH and nC7. The coking rate of MCH was lower than that of nC7 at low temperatures, while the trend was the opposite at high temperatures. The variation in C/H ratio of coke for MCH and nC7 with temperature was the same, whereas the C/H ratio of the former was significantly lower. The unique unimolecular demethylation and intramolecular stepwise dehydrogenation reactions of MCH caused its coking rate to be higher than that of nC7. An experimental method was proposed to determine the coking active site density based on composition and structure of coke. Finally, a coking mechanism based on the growth of spherical coke particles was proposed.